Pengaruh Leverage, Profitabilitas dan Likuiditas terhadap Keputusan Hedging - Luviani, Nur Hannah; Pramiudi, Udi (Jurnal Ilmiah Akuntansi Kesatuan, 2020)
International transactions carried out by companies in Indonesia have some implications related to foreign exchange rates. Fluctuations in foreign exchange rates make the companies experience financial risks resulting in a decrease in profits or an increase in debts, which eventually will raise losses and weaken the financial performance. To avoid these financial risks, companies can make hedging decisions to maintain currency exchange rates and avoid excessive risks. The purpose of this study is to determine and analyze the effects of leverage, profitability and liquidity on hedging decisions in manufacturing companies listed on the Indonesia Stock Exchange in 2015 - 2018. The research method used is a quantitative analysis method with purposive sampling technique. Data are obtained from a research sample of 28 companies. This study uses logistic regression analysis techniques to determine the variables that influence companies in hedging decisions. Secondary data were gathered from the Indonesia Stock Exchange, the companies’ websites and their annual financial statements. The results show that leverage and profitability partially have no effects on hedging decisions, with calculated t scores of 0.578 and 0.198. However, liquidity has an influence on hedging decisions with calculated t score of 0.003. Leverage, profitability and liquidity simultaneously have an influence on hedging decisions with calculated f score of 0.001. Keywords: hedging, leverage, profitability, liquidity